2016
DOI: 10.1371/journal.pone.0158844
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phosphorylated Cyclin-Dependent Kinase 1 Associated with Colorectal Cancer Survival Using Label-Free Quantitative Analyses

Abstract: Colorectal cancer is the most common form of cancer in the world, and the five-year survival rate is estimated to be almost 90% in the early stages. Therefore, the identification of potential biomarkers to assess the prognosis of early stage colorectal cancer patients is critical for further clinical treatment. Dysregulated tyrosine phosphorylation has been found in several diseases that play a significant regulator of signaling in cellular pathways. In this study, this strategy was used to characterize the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…Lingling Wu et al revealed that CDK1 is a positive regulator of the IFN signaling pathway and its overexpression may be the primary mechanism of type I IFN signaling that is abnormally amplified in systemic lupus erythematosus [26]. Peng-Chan Lin et al demonstrated that high levels of CDK1 pTyr15 are associated with prolonged disease-free survival in patients with stage II colorectal tumor, and CDK1 pTyr15 protein may be a potential indicator of colorectal tumor advancement [27]. Xingcheng Chen et al verified that ajuba phosphorylation of CDK1 can promote cell proliferation and tumor formation [28].…”
Section: Introductionmentioning
confidence: 99%
“…Lingling Wu et al revealed that CDK1 is a positive regulator of the IFN signaling pathway and its overexpression may be the primary mechanism of type I IFN signaling that is abnormally amplified in systemic lupus erythematosus [26]. Peng-Chan Lin et al demonstrated that high levels of CDK1 pTyr15 are associated with prolonged disease-free survival in patients with stage II colorectal tumor, and CDK1 pTyr15 protein may be a potential indicator of colorectal tumor advancement [27]. Xingcheng Chen et al verified that ajuba phosphorylation of CDK1 can promote cell proliferation and tumor formation [28].…”
Section: Introductionmentioning
confidence: 99%
“…Our results support the previous findings on the role of phosphorylation studied by the methods of conventional biology [62][63][64].…”
Section: It Is Evident Fromsupporting
confidence: 93%
“…3D and E) and an elevated number of undifferentiated epithelial cells (Fig. 3F), as evidenced by increased epithelial transcript levels of Cdk1 , a gene encoding a cyclin-dependent kinase involved in cell proliferation (20), and decreased epithelial transcript levels of Angptl4 , a gene activated by (peroxisome proliferator-activated receptor gamma (PPARγ) in terminally differentiated epithelial cells (21, 22). Consistent with reduced epithelial differentiation, alcian blue staining revealed a reduction in the number of goblet cells, a terminally differentiated epithelial cell type, in colonic sections from AOM/DSS-treated mice compared to the level in control animals (Fig.…”
Section: Resultsmentioning
confidence: 99%